TINDAK UJAR EKSPRESIF DALAM FILM FREEDOM WRITER KARYA ERIN GRUWELL SUATU KAJIAN PRAGMATIK - ANDREANUS, JANSEN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â  As the requirement to accomplish the Sarjana Degree at the Faculty of Humanities Sam Ratulangi University Manado, this research entitled â€œexpressive act in the Film Freedom Writer by Erin Gruwellâ€ is intended. The focus of this skripsi is on expressive act analysis following the theory of Searle (1979) who divides expressive act into six categories and functions: apologizing, pardoning, praising, thanking, congratulating and condoling. The aims of this analysis are to categorize expressive act and to analyze its functions in the script of the film Freedom Writer by Erin Gruwell. The descriptive method is used in this research the data are categorized and analyzed by using the theory by Searle (1979). The result of this skripsi shows that the functions of expressive acts in the film Freedom Writer by Erin Gruwell are: apologizing, pardoning, praising, thanking, congratulating and condoling.